Carriage of hazardous materials (HM) by sea and the right of innocent passage: states disputes and environmental concerns - Samiotis, Georgios; Grekos, Dimitrios (SPOUDAI Journal of Economics and Business, 2015)
In recent years, the increasing carriage of HM by sea has already leaded to one of the major disputes between coastal and flag States. This is because of the potential damage to the marine environment and the socio-economic aftermath. Furthermore maritime accidents (e.g. M/T Ievoli Sun, M/T Prestige) and experiments at sea (e.g. M/V Cape Ray’s mission and the Syrian Chemical Weapons transportation by sea) introduce extraordinary sea threats. The need to better sea environmental protection will result increasing conflicts among States. In one sense this dispute is thrilling and signals the emergence of new treatment ideas, while in another designates that there is no agreement over how shipping community should proceed to tackle it. The fact is that while the coastal States claim as to the obligation to protect their territorial sea and especially the marine environment, the flag States invoke the right of innocent passage keeping the carriage of HM by sea in the limelight, even if these concepts have been codified in UNCLOS 1982.This new visibility calls for a recalibration of the balance between navigation and environment. JEL Classification: K32, R41, Q53.